Revision of the Aggressiveness dimension of Dimensional Clinical Personality Inventory - Carvalho, Lucas de Francisco (2016)
The present study aimed to review the Aggressiveness dimension of the Dimensional Clinical Personality Inventory (IDCP) in two steps: the first focused on developing new and the second for testing the psychometric properties in a sample of 230 subjects, 176 women, aged between 18 and 63 years, with minimum education of undergraduate (52.6%). The subjects answered the IDCP, the Revised NEO Personality Inventory (NEO-PI-R) and the Personality Inventory for DSM-5 (PID-5). The first step resulted in 47 items, of which 20 were new. The second step resulted in a composite of 16 items, in two interpretable structure components, antagonism and violence, with internal consistency coefficients of .89 for total, and .82 for each component. The analysis of the scale with NEO-PI-R and PID-5 revealed consistent and expected correlations. The data reveal the adequacy of the new Aggressiveness dimension of IDCP.